2018
DOI: 10.4103/pm.pm_213_17
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical evidence for the antitumor potential of Garcinia mangostana Linn. On diethylnitrosamine-induced hepatic carcinoma

Abstract: Background:Garcinia mangostana is extensively used in most of the Indian herbal pharmaceuticals and nutraceuticals.Objective:The objective of this study was to elucidate the underlying biochemical protective mechanism of G. Mangostana Linn. fruit extract (GME) in deterioration of diethylnitrosamine (DEN)-induced hepatic carcinoma (HCC) in rats.Materials and Methods:The cancer was induced using DEN to the experimental rats and treated with GME (200, 400, and 600 mg/kg) to find its anticancer property. The cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Previous studies have demonstrated that 4-shogaol from ginger may be a novel anticancer agent for the treatment of metastasis in breast cancer (Chen, 2019). Garcinol has also shown strong activity against breast cancer and leukemia (Jainu et al, 2018). Bionanotechnology has a pivotal role in the development of a novel therapy in the treatment of cancer (Ke, 2019;Wang, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that 4-shogaol from ginger may be a novel anticancer agent for the treatment of metastasis in breast cancer (Chen, 2019). Garcinol has also shown strong activity against breast cancer and leukemia (Jainu et al, 2018). Bionanotechnology has a pivotal role in the development of a novel therapy in the treatment of cancer (Ke, 2019;Wang, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that 4-shogaol from ginger may be a novel anticancer agent (Chen et al, 2019). Garcinol has also shown strong activity against breast cancer and leukemia (Jainu et al, 2018). Bionanotechnology has a pivotal role in the development of novel therapies (Ke et al, 2019;Wang et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that 4-shogaol from ginger may be a novel anticancer agent for the treatment of metastasis in breast cancer (Chen et al, 2019). Garcinol has also shown strong activity against breast cancer and leukemia (Jainu et al, 2018). Bionanotechnology has a pivotal role in the development of a novel therapy in the treatment of cancer (Ke et al, 2019;Wang et al, 2019).…”
Section: Resultsmentioning
confidence: 99%